Cases Report: Benign Paroxysmal Positional Vertigo (BPPV) - Elvina Zuhir (Lembaga Pengembangan Kinerja Dosen, 2025)
Vertigo is defined as dizziness, namely an unpleasant, moving illusions. A case of a 36 years old woman came to the polyclinic with complaints that her head felt dizzy and spinning since 3 days before entering the hospital and was getting worse. After history, physical and supporting examination, the patients was diagnosed with BPPV.